(untitled) (Journal of Leadership, Accountability and Ethics, 2021)
Duality is the most direct form of control over firm decision-making by CEOs. Yet, while the downstream firm effects of duality have been studied in detail, why certain CEOs are more likely to assume a dual role remains understudied. I propose childhood socio-economic status (SES) as an important driver of a CEO’s propensity to serve as chair of the board. During their upward social transition, CEOs from a low-SES background develop a heightened internal locus of control (i.e., the belief that they themselves are in control of their lives) and consequently become more likely to seek control over their environment. This will be reflected in a higher probability by low-SES CEOs to assume a dual role compared to their non-low SES counterparts. I expect that this relationship will be weakened by factors that act as indirect forms of control over the firm – higher stock price and organizational slack. Drawing on a dataset of Fortune 100 CEOs from 2000 to 2016 I find results in line with the hypothesized relationships.